Postoperative serum magnesium levels as a predictor for the need for calcium replacement after total thyroidectomy: a prospective study - Soares, Carlos Segundo Paiva [UNESP] (2023)
Objective: Our aim was to assess the ability of serum magnesium (Mg), measured on the first postoperative day (Mg1PO), to predict the need for calcium (Ca) replacement in patients undergoing total thyroidectomy (TT). Subjects and methods: Eighty patients undergoing TT, with Mg1PO and PTH dosage in the first (PTH1h) and eighth (PTH8h) hours after TT, were evaluated for the need for Ca replacement. Data were evaluated by uni/multivariate logistic regression and Receiver Operating Characteristic (ROC) curve. Results: 32 patients (40%) required Ca replacement. Median PTH1h, PTH8h and Mg1PO were higher in the no replacement group: 17 versus (vs) 3 pg/mL (p < 0.001), 18.2 vs 3.0 pg/mL (p < 0.001) and 2 vs 1.6 mg/dL (p < 0.001), respectively. Mg1PO was the isolated predictor for this replacement (odds ratio = 0.0004, 95% confidence interval: 0.000003-0.04; p = 0.001), with the cut-off value of 1.8 mg/dL showing sensitivity and specificity of 78.1% and 87.5%, respectively. Conclusions: In this group of patients, serum Mg1PO was the isolated predictor for the need for Ca replacement. Arch Endocrinol Metab. 2023;67(3):355-60.